Wind erosion reduction by water diversion in the lower Heihe River Basin, Northwest China. (15th May 2018) - Yan, Haiming; Zhan, Jinyan; Yang, Huicai; Liu, Wei; Li, Wei
Abstract: The lower Heihe River Basin, a key ecological function zone in Northwest China, has suffered from serious land degradation by wind erosion for decades, posing a great threat to the national ecological safety. This study explores the dynamics of wind erosion and the soil conservation service (SCS) in this region following water diversion during 2001–2010 with the statistic model of wind erosion on small watershed basis based on remote sensing, climate, and soil data, and impacts of driving factors on the SCS are revealed with scenario analysis. Results suggest that the SCS represented by the soil retention amount was less than 500 t km −2  yr −1 in most parts of the study area and higher than 15, 000 t km −2  yr −1 in a few wind erosion hotspots, including the East Juyanhai region, Dingxin Oasis, Ejina Oasis, and its surrounding desert–oasis transitional areas. The cumulative potential soil loss of the study area increased much faster than the cumulative soil retention amount, and fractional vegetation cover influenced by the Ecological Water Diversion Project played a dominant role in improving the SCS, accounting for 82.25% of the change in the SCS of the study area. Climate change played a subordinate role, but there were essential separate and interactive effects of climate factors on the SCS. This study provides a preliminary overview of hotspots of wind erosion and the SCS in the lower Heihe River Basin from a geographical perspective, laying a solid basis for combating land degradation by wind erosion in arid regions of Northwest China.